Simulation Study on the Influence of Drag Reducing Agent on Oil Mixing Segment in Product Oil Pipeline Transportation - Li, Yayang (Scientific Journal of Technology, 2026)
Drag reducing agents (DRAs) play a vital role in reducing flow resistance, improving transportation efficiency, and saving energy consumption in product oil pipeline transportation. During long-distance transportation, product oil usually operates in a turbulent state, and turbulent fluctuations and energy dissipation inside the fluid are the main causes of pressure drop along the pipeline. As high-molecular polymers, DRAs can interact with turbulent structures, attenuate turbulent fluctuations, and reduce energy loss, thereby achieving drag reduction and throughput enhancement. Meanwhile, DRAs also exert certain effects on fluid viscosity and flow field structure, making the flow regime more stable, which presents favorable engineering application value. In this paper, a numerical model of DRA injection into product oil pipelines is established based on FLUENT software to investigate the flow, mixing, and diffusion processes of DRAs in pipelines. By adjusting parameters such as injection angle, injection pipe diameter, injection flow rate, and injection position, the distribution characteristics of DRAs and their influences on the flow field under different working conditions are compared and analyzed. The results show that a reasonable injection scheme can promote uniform distribution of DRAs in the pipeline and improve the mixing degree with the main flow oil, thus enhancing the drag reduction effect. In summary, focusing on the application of DRAs in product oil pipelines, this paper conducts research from both mechanism analysis and numerical simulation, and analyzes the flow characteristics of DRAs in pipelines and their influence laws on the oil mixing segment. The research results can provide a reference for the optimization of DRA injection modes and the control of product oil batch transportation process, which is of certain engineering significance for improving pipeline operation efficiency and reducing transportation costs.